Estudio Descriptivo Sobre La Influencia De Las Variables Personales Y El Fracaso Escolar En La Ciudad AutÃ³noma De Melilla - Estrada de Madariaga, MÂª del Mar; Trujillo Torres, D. Juan Manuel (European Scientific Journal, ESJ, 2016)
The analysis of this study has been approached through a questionnaire. The questionnaire consists of two parts. The first is personal and academic data. The second part of the questionnaire contains 46 items. It is a Likert scale of four alternatives. For the statistical treatment of the data it was used SPSS v.21 for Windows. For the two-dimensional descriptive statistical analysis it was used the Mann-Whitney and Kruskal-Wallis programs. The most relevant contributions, in which the theoretical framework of this research is based, have been the Diagnostic and Statistical Manual of Mental Disorders, 2014 (DSM-5); Educational Law, especially that related to diversity, as well as the different contributions of studies and doctoral theses related to the investigation. From this study, intervention proposals and new lines of research will be carried out in order to reduce the high rate of failure and early school dropout in this city.